The role of relationship marketing in Small and Medium Enterprises (SMEs) - Handriana, Tanti (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examines the role of relationship marketing on Small and Medium Enterprises (SMEs) in Indonesia. Relationship marketing is a concept in marketing management aimed at maintaining long-term relationships with customers. Meanwhile, SMEs occupy a crucial role in sustaining the economy of Indonesia. Therefore, by implementing the concept of relationship marketing, it is expected that customer loyalty on SMEs is formed and can maintain the sustainability of SMEs. The study used survey methods, with a sample pool of 183 SMEs customers. The analysis technique utilized structural equation modeling (SEM) and the data was processed using AMOS Basic. The results show that trust and relational commitment is significantly affected by communication and relational benefits. Meanwhile, trust and relational commitment significantly affect customer loyalty. The variables of similarity and frequency of interactions have no significant effect on either trust or relational commitment of customers of SMEs.